Labor Adjustment Under Different Institutional Structures: A Case Study of Germany and the United States - Susan N. Houseman; Katharine G. Abraham (W.E. Upjohn Institute for Employment Research, 1994)
Like most Western European countries, Germany stringently regulates dismissals and layoffs. Critics contend that this regulation raises the costs of employment adjustment and hence impedes employers' ability to respond to fluctuations in demand. Other German labor policies, however, most especially the availability of unemployment insurance benefits for those on short time, facilitate the adjustment of average hours per worker in lieu of layoffs. Building on earlier work, we compare the adjustment of employment, hours and inventories to demand shocks in the German and U.S. manufacturing sectors. We find that, in the short run, whereas U.S. employers rely principally on the adjustment of employment levels to respond to demand shocks, German employers rely principally on the adjustment of average hours per worker. The adjustment of overall labor input is generally similar in the two countries. Short-time work makes a very important contribution to short-run hours adjustment in Germany. We find little evidence that inventories help to buffer demand fluctuations in either country. Our findings suggest that, given appropriate supporting institutions, strong worker job security can be compatible with employers' need for flexibility in staffing levels.
Additional information: A revised version of this paper appears in F. Butler, et al., eds. Institutional Frameworks and Labor Market Performance: Comparative Views on the U.S. and German Economies. London: Routledge, 1995. Please cite the revised version.
Keywords: J23; J65; J83; 330; labor; adjustment; layoffs; Germany; work; hours